D's Pastries / Muhammad Daniel Imran Ramlan and Saiful Johanies Daniel Saiful Amri - Ramlan, Muhammad Daniel Imran; Saiful Amri, Saiful Johanies Daniel (2022)
‘The best bakery and pastry shop in the country!’ This is what we envision to be in the future. Our business, D’s Pastries, sells a variety of pastries and delicacies ranging from fruit tarts to mini beef lasagnes. We sell products that are not only sweet, but also savoury and very filling. Our products are all affordable and reasonable and can be purchased by customers of all levels of income. Our business uses Facebook as our main medium of carrying out our business activities such as promoting our products, selling our products, information of our business and our products, information on deals and promotions. We also hope to retain old customers and to attract new and potential customers in the future. We also aim to gain enough profit to open our own shop lot in the future.